Effectiveness of a pedagogical module for the process of weaning from mechanical ventilation in advanced nursing education - Sakinah Awangharun; Norlidah Alias (PLoS ONE, 2026)
Background Pedagogical module for weaning process from mechanical ventilation (WPMV) is the specific need for advanced nursing education in cardiothoracic intensive care unit (CICU). The CICU nurses need to have Advanced nursing personnel in the CICU require comprehensive theoretical knowledge and applied clinical reasoning skills including patient data analysis, structural decision-making, and care decision justifications to safely adjust ventilator settings following cardiothoracic surgery. However, currently no specific a pedagogical module for advanced nursing education used for CICU in Malaysia. Aim To investigate the effectiveness of a structured pedagogical module for WPMV in improving knowledge and applied clinical reasoning among Cardiothoracic Intensive Care Unit (CICU) nurses. Methods This study utilizes a quasi-experimental, non-randomized pre-post design. A total of 24 CICU nurses participated. Participants were grouped based on an institutional competency threshold of 70%, which reflects the standard passing criterion for clinical assessments in the study setting. The 70% cutoff represents the standard institutional passing threshold established by the Medical Education and Nursing Division at the National Heart Institute (IJN) for postgraduate clinical assessments and unit privilege. This study focuses primarily on within-group changes following the intervention, while the comparison group is used as a performance benchmark rather than for inferential comparison. Results The implementation of the pedagogical module led to a statistically significant improvement in participants’ knowledge and applied clinical reasoning. Participants in the intervention group demonstrated a statistically significant improvement in theoretical scores (mean difference = 37.63, p < 0.001). The large effect size indicates substantial educational impact. Due to the small and unequal group sizes, between-group comparisons were interpreted descriptively rather than inferentially. Conclusion The WPMV pedagogical module significantly improves theoretical knowledge and applied clinical reasoning among CICU nurses. However, conclusions are limited to educational outcomes, and further research is required to evaluate its impact on clinical practice and patient outcomes.